Analysis of Steam Power Generators in Fulfilling Electricity Needs: A Case Study at PT Madubaru Yogyakarta, Indonesia - Danis Dwi Istiawan; Ramadoni Syahputra; Karisma Trinanda Putra (Universitas Muhammadiyah Yogyakarta, 2017)
This research was conducted to find out the amount of power produced by steam power generators and the amount of power needed for the operation of production motors in PT Madubaru Yogyakarta. This study also discusses the factors that support and inhibit the fulfillment of electric power in PT Madubaru Yogyakarta. From the results of the analysis that has been done, it can be seen that the power generated by the steam power generator at PT Madubaru Yogyakarta can meet the electricity needs of production motors in the factory. The power generated by the three steam generators at PT Madubaru amounts to 3,000 KW, while the power needed for the operation of production motors at the Milling Station, the Ketel Station, Central Factory Station, and Rear Factory Station is 2,313.54 KW. However, the production motor does not always turn on simultaneously, so the power needed is between 1,500 KW to 2,000 KW. The remaining power is used to anticipate an increase in electricity load.